Database resources of the national center for biotechnology information - Sayers, Eric W; Bolton, Evan E; Brister, J Rodney; Canese, Kathi; Chan, Jessica; Comeau, Donald C; Connor, Ryan; Funk, Kathryn; Kelly, Chris; Kim, Sunghwan; Madej, Tom; Marchler-Bauer, Aron; et al. (Nucleic acids research, 2022)
Abstract The National Center for Biotechnology Information (NCBI) produces a variety of online information resources for biology, including the GenBank® nucleic acid sequence database and the PubMed® database of citations and abstracts published in life science journals. NCBI provides search and retrieval operations for most of these data from 35 distinct databases. The E-utilities serve as the programming interface for the most of these databases. Resources receiving significant updates in the past year include PubMed, PMC, Bookshelf, RefSeq, SRA, Virus, dbSNP, dbVar, ClinicalTrials.gov, MMDB, iCn3D and PubChem. These resources can be accessed through the NCBI home page at https://www.ncbi.nlm.nih.gov.